Scalable monitoring support for resource management and service assurance. - Asgari, A. (IEEE Network : the magazine of global information exchange)
Continuous monitoring of network status and its resources are necessary to ensure proper network operation. Deployment of QoS-based value-added services in IP networks necessitates the employment of resource management techniques and specifically the use of traffic engineering. The latter typically relies on monitoring data for both offline proactive and dynamic reactive solutions. The variety of data to be collected and analyzed using different measurement methods and tools, and the extent of monitoring information to use demand a proper QoS monitoring infrastructure. A monitoring system should be scalable in terms of network size, speed, and number of customers subscribed to value-added services. This article investigates the requirements of scalable monitoring system architectures, proposes principles for designing such systems, and validates them through the design and implementation of a scalable monitoring system for QoS delivery in IP differentiated services networks. Experimental assessment results prove the accuracy and scalability of the proposed monitoring system.